PENGARUH KARAGENAN TERHADAP KARAKTERISTIK FISIK DAN KIMIA GEL CINCAU HIJAU POHON (Premna oblongifolia Merr.) - Windi Atmaka; Kelvin Muhammad Akbar; Bara Yudhistira; Sigit Prabawa (Agroindustrial Technology, University of Trunojoyo Madura, 2020)
Green grass has several bioactive content as well as the main fiber components of pectin. Green grass cincau are traditionally made for the filling of jelly that is beneficial to the digestion and health. Green grass jelly is easy to in decrease quality caused by internal and external factors. Addition of Hydrocolloidal such as Caragenan is expected to combine with green grass to produce more quality jelly. The aim of this research to know the influence of the Kappa-type Caragenan to the physical and chemical characteristics of green grass jelly. Experimental design in research using complete random design (RAL) with 1 treatment factor. For the addition of Kappa carrageenan, used 0.30%, 0.40%, 0.50% and 0.60%. Physical and chemical characteristics are analyzed, water content, ash content, pH value, crude fiber, antioxidant, syneresis, texture and yield. The result is that more and more the addition of Kappa Caragenan ash content, pH value, crude fiber content, antioxidant values, synergy and texture parameters are increasing in value. As for water content does not show difference and the yield parameter indicates decrease in value.